PROFILE IMPLEMENTASION OF AUTHENTIC ASSESSMENT BY BIOLOGY TEACHER’S CLASS X VOCATIONAL HIGH SCHOOL PHARMACY IKASARI PEKANBARU IN ACADEMIC YEARS 2014/2015 - Pakpahan, Tresia Pakpahan Tresia; Syafii, Wan Syafii Wan; Arief, Raja Hussien Arief Hussien (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this study was to describe Biology teacher’s implementation of authentic assessment profile at Vocational High School Pharmacy Ikasari Pekanbaru. This study held on September 2014 until December 2014. The subject of this research was Biology teacher of class X Pharmacy SMK Pharmacy Ikasari Pekanbaru. The data collecting techniques used in this reasearch were questionnaire and observation. The questionnaire consists of 51 items and three indicators. The indicator are, (I) Objectives, benefits and principles of authentic assessment, (II) Three aspects of authentic assessment, (III) Seven form of authentic assessment. Descriptive study was implemented in this study. Profile implementation of authentic assessment at class X SMK Pharmacy Ikasari Pekanbaru in learning process the result showed that biology teachers’ were: (I) The assessment was implemented in accordance with the objectives, benefits and principles of authentic assessment was very good category (100%). (II) Cognitive assessment was good category (79%), affective was good category (75%), psychomotor was good enough category (55%). (III) Implementation of seven forms of authentic assessment in the subjects of Biology class X Pharmacy SMK Pharmacy Ikasari Pekanbaru: a written assessment was very good category (90%), attitudes assessment was good category (75%), self assessment was good category (75%), assessment of performance was good category (75%), project assessment was good category (75%), products assessment was good category (75 % ), portofolio assessment was good category (75%). An overall, biology teachers’ of class X Pharmacy SMK Pharmacy Ikasari able to organize an authentic assessment in biology learning process in accordance with the implementation of the curriculum 2013.Key words: authentic assessment, vocational high school pharmacy ikasari, biology teacher